Criminal activities as threats to security in the Caribbean - Dawkins-Cavazos, Marika (The Palgrave handbook of Caribbean criminology, 2024)
This chapter presents an overview of the main criminal activities posing threats to security in the Caribbean region. How best to assess Caribbean security realities, the types of security threats, and the strategies employed to combat such threats in the region that are influenced by its strategic location and proximity to the United States are discussed. Information on criminal activities came from various government reports, the United Nations Office on Drugs and Crime, news reports, and articles. The overall evidence suggests that criminal activities in the region undercut the law and weaken socio-economic and political stability that subsequently threaten Caribbean security. Steps to address criminal activities and security in the Caribbean region are suggested.